Does MAX Anomaly Exist in Emerging Market: Evidence from the Turkish Stock Market? - Haykir, Ozkan (International Journal of Economics and Financial Issues, 2018)
In this paper, I investigate a recent asset pricing anomaly proposed by Bali et al. (2011) in the Turkish stock markets during the period between January 2011 and December 2017 using univariate and bivariate sorting methodologies. Bali et al. (2011) suggest that there is a negative link between maximum daily return and future expected a return. If an investor constructs a hedge portfolio buying stocks which are in the highest maximum daily return portfolio and shorting stocks which are in the lowest maximum daily return portfolio, they get the negative payoff at the end of the next month. Results of this study suggest that the MAX anomaly does not exist in Turkish stock markets. Keywords: MAX effect; Extreme return; Turkish stock market. JEL Classifications: G11; G12; G17.